2017
DOI: 10.3390/ijms19010016
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-Gallate Suppresses Human Herpesvirus 8 Replication and Induces ROS Leading to Apoptosis and Autophagy in Primary Effusion Lymphoma Cells

Abstract: Epigallocatechin-3-gallate (EGCG), the major constituent of green tea, has been shown to induce cell death in cancer cells. Primary effusion lymphoma (PEL) is an aggressive neoplasm caused by human herpesvirus 8 (HHV8). In this study, we examined the role of EGCG on PEL cells in cell death and HHV8 replication. We performed trypan blue exclusion assay to assess the cell viability of PEL cells, flow cytometry analysis to examine the cell cycle distribution and reactive oxygen species (ROS) generation, caspase-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 40 publications
1
45
0
Order By: Relevance
“…It also induces apoptosis in human oral cancer KB, head and neck cancer FaDu, NSCLC A549, and breast cancer MCF-7 cells [96,97]. Besides, EGCG induces autophagy, and inhibition of autophagy can enhance EGCG-induced cell death in human mesothelimoa ACC-meso, Y-meso, EHMES-10, EHMES-1 and MSTO-211H, and primary effusion lymphoma BCBL-1 and BC-1 cells [98,99]. In contrast, it induces cell death via apoptosis and autophagy in oral squamous cell carcinoma SCC-4 cells [84], so autophagy plays a dual role in EGCG-induced cell death.…”
Section: Epigallocatechin Gallate (Egcg)mentioning
confidence: 99%
“…It also induces apoptosis in human oral cancer KB, head and neck cancer FaDu, NSCLC A549, and breast cancer MCF-7 cells [96,97]. Besides, EGCG induces autophagy, and inhibition of autophagy can enhance EGCG-induced cell death in human mesothelimoa ACC-meso, Y-meso, EHMES-10, EHMES-1 and MSTO-211H, and primary effusion lymphoma BCBL-1 and BC-1 cells [98,99]. In contrast, it induces cell death via apoptosis and autophagy in oral squamous cell carcinoma SCC-4 cells [84], so autophagy plays a dual role in EGCG-induced cell death.…”
Section: Epigallocatechin Gallate (Egcg)mentioning
confidence: 99%
“…The role of epigallocatechin-3-gallate on lymphoma cells in cell death was evaluated. Results demonstrated that epigallocatechin-3-gallate caused induction of cell death and reactive oxygen species generation in lymphoma cells [ 116 ].…”
Section: Role Of Egcg In Inhibition and Prevention Of Various Typementioning
confidence: 99%
“…EGCG exhibits antioxidant as well as pro-oxidant properties. Evidences in the literature suggest that the prooxidant activity of EGCG may account for its anti-proliferative and cancer therapeutic effects [ 26 ]. We observe that EGCG treatment can significantly increase the frequency of CIN in COLO205 cells ( Table 2 , Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%